2009
DOI: 10.1111/j.1751-2980.2009.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CagA status of Helicobacter pylori and serum levels of interleukin (IL)‐17 and IL‐23 in duodenal ulcer patients

Abstract: OBJECTIVE:It has been reported that the cytotoxinassociated gene A (cagA+) H. pylori strains induce severe gastric mucosal inflammation. The aim of this study was to investigate the association of the virulence factor CagA with IL-17 and IL-23 serum levels in duodenal ulcer (DU) patients and H. pylori-infected asymptomatic (AS) carriers. METHODS:In total, 45 H. pylori-infected DU patients were enrolled to study: 23 tested positive for the anti-CagA antibody (anti-CagA+) and 22 tested negative for the anti-CagA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…A close relationship was also indicated between H. pylori CagA + strains with PU disease and the expression of the inflammatory and pathological parameters . Higher levels of inflammatory cytokines such as TNF‐α, IL‐8, IL‐17, and IL‐18 were also indicated in H. pylori ‐infected patients, especially in those infected with CagA + strain of bacteria IL‐18 …”
Section: Discussionmentioning
confidence: 75%
“…A close relationship was also indicated between H. pylori CagA + strains with PU disease and the expression of the inflammatory and pathological parameters . Higher levels of inflammatory cytokines such as TNF‐α, IL‐8, IL‐17, and IL‐18 were also indicated in H. pylori ‐infected patients, especially in those infected with CagA + strain of bacteria IL‐18 …”
Section: Discussionmentioning
confidence: 75%
“…It is believed that the release of proinflammatory cytokines, e.g., Interleukin-1 (IL-1), IL-8, IL-17, IL-23 and Tumor Necrosis Factor-ά (TNF-ά), stimulated by H. pylori infection plays a role in the chronic inflammation of bronchi (Roussos et al, 2006;Jafarzadeh et al, 2009;Cornwell et al, 2010). Moreover, serum levels of these cytokines normalize following eradication therapy of H. pylori (Kountouras et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CagApositive strains of H. pylori were more potent than CagA-negative strains in TLR2-induced cytokine secretion from macrophages, indicating the contribution of CagA or other PAI-associated genes in TLR2-related cytokine production [57]. The results of a number of studies show that the expression of pro-inflammatory cytokines and mediators were higher in infected subjects with CagA-positive strains than CagA-negative strains [13,14,58,59]. Experimentally, it has been also demonstrated that the IL-6 and IL-1β secretion by bone-marrow derived macrophages in response to H. pylori is mediated by TLR2 [31].…”
Section: H Pylori Induces Tlr2-related Signaling In Macrophagesmentioning
confidence: 94%